Explaining happiness trends in Europe by welfare policies and economic growth: Easterlin and O'Connor revisited - Heinz Welsch (University of Oldenburg, Department of Economics, 2024)
Easterlin and O'Connor (PNAS 2022) have investigated which economic, social, political, and ecological factors explain long-run (36-year) changes in European countries' happiness (life satisfaction). Considering six potential predictors advanced in the pertinent literature, they found only rising welfare state generosity to be significantly associated with rising happiness. Noticing a salient characteristic of the data used - a strong and significant association between happiness trends and initial happiness levels - I modify this analysis by controlling for initial happiness levels and by considering long-run relative changes in addition to absolute changes in happiness. Both modifications respond to the circumstance that happiness scales are bounded so that it is hard for happiness to increase - especially in absolute terms - if it is already high. I find the inclusion of initial happiness to greatly increase the explanatory power (R 2) of the regression models considered and, as a consequence, to raise the precision of coefficient estimates. Due to increased precision, not only welfare state generosity but also growth in per-capita GDP is found to significantly predict both absolute and relative long-run changes in countries' happiness, whereas other candidate explanatory variables remain insignificant. Welfare state generosity and GDP growth are not only statistically, but also economically significant.
Keywords: I31; D60; H53; I38; O10; O52; 330; happiness; life satisfaction; welfare policy; economic growth; Easterlin Paradox